2019
DOI: 10.1177/1066896919888578
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Carcinosarcoma: Clinicopathologic Features of 2 Cases

Abstract: This study reports 2 odontogenic carcinosarcomas, including the clinicopathologic and immunoprofile characteristics of these rare tumors. The first case occurred in a 22-year-old male presenting a bilobular mass involving the gingiva and bone of the premolar region of the left mandible, with paresthesia of the lower lip. Microscopic examination revealed a tumor similar to ameloblastic fibrosarcoma, with atypical mesenchymal cells; however, the odontogenic epithelium also showed atypia. In the second case, a 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The proliferative index Ki-67 in our case was around 7.5% in the epithelial component and 3% in the ectomesenchymal component. This is in accordance with the work of Dos Santos et al (2018) and Soares et al (2019), who found that Ki-67 index was higher in the epithelial component than the ectomesenchymal component [4][5][6][7] .…”
Section: Ocs Must Be Distinguished From Ameloblastic Fibrosarcoma Insupporting
confidence: 92%
See 4 more Smart Citations
“…The proliferative index Ki-67 in our case was around 7.5% in the epithelial component and 3% in the ectomesenchymal component. This is in accordance with the work of Dos Santos et al (2018) and Soares et al (2019), who found that Ki-67 index was higher in the epithelial component than the ectomesenchymal component [4][5][6][7] .…”
Section: Ocs Must Be Distinguished From Ameloblastic Fibrosarcoma Insupporting
confidence: 92%
“…The current case showed multiple radiopacities; may be due to the preexisting immature odontoma. atypia, and spindle cell variant of ameloblastic carcinoma, which lacks the ectomesenchymal component [2][3][4][5][6][7][8] . In the present case, there was a patchy positive expression of vimentin in the epithelial component.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations